A Subgrain‐Size Piezometer Calibrated for EBSD. Issue 23 (7th December 2020) - Goddard, R. M.; Hansen, L. N.; Wallis, D.; Stipp, M.; Holyoke, C. W.; Kumamoto, K. M.; Kohlstedt, D. L.
Abstract: We calibrate a subgrain‐size piezometer using electron backscatter diffraction (EBSD) data collected from experimentally deformed samples of olivine and quartz. Systematic analyses of angular and spatial resolution test the suitability of each data set for inclusion in calibration of the subgrain‐size piezometer. To identify subgrain boundaries, we consider a range of critical misorientation angles and conclude that a 1° threshold provides the optimal piezometric calibration. The mean line‐intercept length, equivalent to the subgrain‐size, is found to be inversely proportional to the von Mises equivalent stress for data sets both with and without the correction of Holyoke and Kronenberg (2010, https://doi.org/10.1016/j.tecto.2010.08.001 ). These new piezometers provide stress estimates from EBSD analyses of polymineralic rocks without the need to discriminate between relict and recrystallized grains and therefore greatly increase the range of rocks that may be used to constrain geodynamic models. Plain Language Summary: Understanding the tectonic stress in lithospheric plates is key to evaluating a breadth of geological phenomena, such as the evolution of major ductile shear zones. One method of estimating past stress magnitudes is to measure microstructural features that vary systematically with the applied stress, a technique known as "piezometry." Several piezometers have been calibrated based on the size of recrystallized grains in a rock, but they are limited to domains consisting of only a single mineral, as the presence of multiple minerals inhibits grain growth. Subgrains, however, are features inside individual grains and are unaffected by the presence of other minerals. We use electron backscatter diffraction (EBSD), a scanning electron microscopy technique, to quantify the relationship between subgrain size and stress in rocks that have been deformed in a laboratory under controlled conditions, providing the first subgrain‐size piezometer calibrated for EBSD. In addition, unlike many piezometers that are calibrated for a single mineral, our piezometer can be applied to each mineral in a rock. This piezometer offers the potential to investigate the macroscopic stress and microscopic stress distributions in a wide range of rock types. Key Points: We present a new subgrain‐size piezometer calibrated for EBSD, with a 1° critical misorientation angle This subgrain‐size piezometer can be applied to multiple minerals and appears to be independent of the deformation geometry This subgrain‐size piezometer should be unaffected by the presence of secondary minerals and thus applicable to polymineralic rocks